New organisational trends at the Universiteit Van Amsterdam - Bleijerveld, R.H.T. (Ruud) (REBIUN, 2003)
At the Universiteit van Amsterdam the developments in the field of ICT have led to major changes in the organisation of supportive services for education and research. The consequences are particularly significant for the library, which sees itself transformed from a ‘passive’ source of information into an active multimedia knowledge provider. The development of Learning Resources Centres, supported by the library, is in full swing and it is fascinating to see the close collaboration evolving between faculty, IT specialists, communication professionals, library staff and publishers. The measure of success proves to relate strongly to the physical design and furnishing of the location, which is in turn determined by the given architectural - and financial - parameters. The didactical concept is the leading principle.
Keywords: Universiteit van Amsterdam; Espacio Europeo de Educación superior (EEES)